Beyond costume tradition and physical computing: characterizing the profile of interactive costume creators. Issue 2 (3rd April 2021) - Honauer, Michaela
ABSTRACT: Interactive costumes enrich performance concepts and means of artistic expression. However, their creation challenges costume designers and technicians because they demand expertise in interaction design and electronic engineering. This article aims at empowering performance professionals to exploit the full potential of interactive costumes by discussing the creation process from the creators' perspectives. Insights from expert interviews highlight that costume design combined with interaction design underlies the profile of interactive costume designers, whilst costume construction combined with electronic engineering underlies the profile of interactive costume technicians . Together, these profiles are capable of creating interactive costumes if complemented with expertise in e-textiles and body-centred design and development approaches. The findings suggest that teamwork between disciplines is essential, resulting ideally in transcending disciplinarity through shared practices, and using diverse methods, materials, and knowledge. All of this might evoke a paradigm shift in the practice and education of costume creators and other respective professions.